1995
DOI: 10.1016/0895-7061(95)00217-0
|View full text |Cite
|
Sign up to set email alerts
|

Plasma adrenomedullin in patients with primary aldosteronism

Abstract: Adrenomedullin (AM) is a novel hypotensive peptide originally isolated from the pheochromocytoma tissue of humans. To examine the pathophysiological role of AM in primary aldosteronism (PA), the plasma concentration of AM in patients with PA was measured with a specific radioimmunoassay and compared to that in age- and sex-matched healthy normotensive subjects. In addition, the concentrations of AM as well as catecholamines in the plasma from both the adrenal vein and the inferior vena cava (IVC) were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…The GH subgroup, which has not been previously studied, was included because of the potential difference in etiology compared with preeclampsia. 29 Other hypertensive diseases, including essential hypertension, [11][12][13] renal failure, 11 heart failure, 12,13 and primary aldosteronism, 14 all show an increase in plasma ADM levels. In these conditions, ADM may serve to compensate for the elevation of blood pressure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The GH subgroup, which has not been previously studied, was included because of the potential difference in etiology compared with preeclampsia. 29 Other hypertensive diseases, including essential hypertension, [11][12][13] renal failure, 11 heart failure, 12,13 and primary aldosteronism, 14 all show an increase in plasma ADM levels. In these conditions, ADM may serve to compensate for the elevation of blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…A paracrine or autocrine mode of action of ADM has been inferred from the elevated concentrations found in fetoplacental tissues. 18 We hypothesized that maternal plasma ADM levels should, as in other hypertensive disorders, 11,12,14 be higher in hypertensive pregnancies than in normotensive pregnancies and that the higher placental resistance found in preeclamptic pregnancies results not from a lack of locally produced ADM but from blunted activity of ADM on the vasculature. Therefore, we sought to evaluate maternal plasma ADM levels and the effect of ADM on placental arteries in both preeclamptic and normal pregnancies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We and one other research group have previously reported this phenomenon. 18,19 The underlying mechanism remains to be elucidated: there may be a mutual relationship between aldosterone and AM. Aldosterone stimulates AM production in rat aortic adventitia or cardiac fibroblasts; increased AM, in turn, regulates the proliferative action of aldosterone in those cells.…”
Section: Effects Of Adrenomedullin In Primary Aldosteronismmentioning
confidence: 99%
“…9 Recently, it was reported that patients with hypertension show high levels of plasma AM compared with normotensive control subjects. [10][11][12][13] Nevertheless, the exact physiopathological role of AM in human hypertension remain to be established.…”
Section: Introductionmentioning
confidence: 99%